Pengaruh Imbal Jasa Penjaminan dan Rasio Profitabilitas Terhadap Pertumbuhan Laba PT. Jamkrindo Cabang Makassar - Nasrun, Nasya; Rustam, Andi; Adiningrat, Andi Arifwangsa (Universitas Teuku Umar, 2025)
This quantitative study aims to analyze the effect of guarantee fees and profitability ratios on profit growth of PT. Jamkrindo Makassar Branch using secondary data from financial statements for the period 2019-2023 and multiple linear regression techniques. The results of the study indicate that guarantee fees and profitability simultaneously affect profit growth. Partially, guarantee fees have a positive and significant effect on profit growth, indicating that increasing service fee income increases the company's profit. Likewise, the profitability ratio has a positive effect on profit growth, where high ROA reflects the company's improving performance and has a positive impact on profit growth.Keywords: Guarantee Fees, Profitability Ratio, Profit Growth